2021
DOI: 10.5433/1679-0359.2021v42n6p3497
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative losses and chemical composition and in vitro digestibility of corn grain silage rehydrated with water or acid whey combined with bacterial-enzymatic inoculant

Abstract: This study aimed to evaluate the effects of rehydration with water or acid whey, as well as the effects of bacterial-enzymatic inoculant on fermentation losses, aerobic stability, and chemical composition and in vitro digestibility of corn grain silages. The treatments consisted of corn kernels (Zea mays) ground through a 3-mm sieve and rehydrated with chlorine-free water or unsalted whey (NaCl) combined or not with bacterial-enzymatic inoculant. This was a 2 x 2 factorial completely randomized design with sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Although it is not possible to compare NDF content before and after ensiling in this review because there are no data on the chemical composition of the mass before ensiling, previous studies, such as that of Rezende et al [42], indicate greater reductions in NDF in silage when whey is used to rehydrate corn grains when compared to water. However, Sousa et al [44] and Cruz et al [45] found different effects of whey compared to water, making it difficult to evaluate this additive's intrinsic effect in reducing the silage's NDF content.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although it is not possible to compare NDF content before and after ensiling in this review because there are no data on the chemical composition of the mass before ensiling, previous studies, such as that of Rezende et al [42], indicate greater reductions in NDF in silage when whey is used to rehydrate corn grains when compared to water. However, Sousa et al [44] and Cruz et al [45] found different effects of whey compared to water, making it difficult to evaluate this additive's intrinsic effect in reducing the silage's NDF content.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pH measurements, concentrations of organic acids, alcohols, N-NH 3 , and quantification of microbial populations are most used to assess silage fermentation [45]. In this review, it was impossible to include the N-NH 3 concentration of silages since the data obtained in the studies presented different ways of quantification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Santos et al [50] have also detected a much lower CF content of SBM after fermentation. Animals such as pigs do not secrete cellulase or hemicellulase in stomach and small intestine and have very limited ability to digest cellulose and hemicellulose, which is only accomplished by microbial fermentation in the cecum and colon [51]. Thus, feeds containing large amounts of CF generally with a coarse texture and poor palatability are difficult to digest.…”
Section: Discussionmentioning
confidence: 99%